Potential and methods of target cholesterol level achievement in daily clinical practice: results of the Russian multi-centre observational study “TREAT TO GOAL” - V. O. Konstantinov (Кардиоваскулярная терапия и профилактика)
Aim. To study potential therapeutic approaches to the management of coronary heart disease (CHD) patients with hypercholesterolemia (HCH), who receive statins, but do not achieve target levels of total cholesterol (TCH) and low-density lipoprotein cholesterol (LDL-CH) in daily clinical practice. Material and methods. The research project “Treat To Goal” is an observational study, involving 10 clinical centres in 6 Russian cities. In total, the study included 712 patients with CHD and HCH (386 men and 324 women; mean age 59 years), who received statins as secondary prevention measure, but did not achieve target levels of TCH and LDL-CH. Results. In order to achieve target TCH levels, the lipid-lowering therapy was modified as follows: 42,4 % patients were administered a new statin; in 32,1 %, the “old” statin dose was titrated; in 25,5 %, statin therapy was combined with ezetimibe. The target TCH levels were achieved, respectively, in 33,5 %, 37,4 %, and 50,4 % of the patients. All three types of therapy modification were well tolerated and safe.Conclusion. Combined lipid-lowering therapy with ezetimibe and statins is the optimal treatment option for Russian patients with CHD and HCH, who otherwise cannot achieve the target levels of blood lipids.